The effects of the use of acetylene gas as an alternative fuel in a gasoline engine_x000D_ - (:unkn) unknown (My University, 2020)
In internal combustion engines, the use of gas fuels is becoming widespread due to its advantages such as low cost and being more environmentally friendly. Acetylene is one of the gas fuels seen as an alternative to petroleum-based fuels in internal combustion engines. In this experimental study, the availability of acetylene gas, a gas fuel, at 1600 rpm, 2400 rpm and 3200 rpm engine speeds in a spark plug-fired engine was investigated. Acetylene gas was added to gasoline by 5% and 10% of the mass and its effect on exhaust emissions was studied. The results showed that adding acetylene gas to gasoline by mass increased CO, CO2 and NOx emissions and exhaust gas temperature. HC, oxygen emissions and air supply coefficient decreased.